2015
DOI: 10.1124/mol.115.098764
|View full text |Cite
|
Sign up to set email alerts
|

Model Organisms in G Protein–Coupled Receptor Research

Abstract: The study of G protein-coupled receptors (GPCRs) has benefited greatly from experimental approaches that interrogate their functions in controlled, artificial environments. Working in vitro, GPCR receptorologists discovered the basic biologic mechanisms by which GPCRs operate, including their eponymous capacity to couple to G proteins; their molecular makeup, including the famed serpentine transmembrane unit; and ultimately, their three-dimensional structure. Although the insights gained from working outside t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 99 publications
1
20
0
Order By: Relevance
“…In line with this model, overexpression of wildtype but not nonpolymerizing lama2 (the gene encoding the achain of Laminin-211) could suppress myelin defects in gpr126 hypomorphic mutants. This, coupled with the dynamic culture assays described above, supports the notion that Laminin-211 polymerization could be one mechanism that facilitates GPR126-NTF removal in vivo (see also Langenhan et al, 2015).…”
Section: In Vivo Mechanisms Of Agpcr Activationsupporting
confidence: 59%
See 1 more Smart Citation
“…In line with this model, overexpression of wildtype but not nonpolymerizing lama2 (the gene encoding the achain of Laminin-211) could suppress myelin defects in gpr126 hypomorphic mutants. This, coupled with the dynamic culture assays described above, supports the notion that Laminin-211 polymerization could be one mechanism that facilitates GPR126-NTF removal in vivo (see also Langenhan et al, 2015).…”
Section: In Vivo Mechanisms Of Agpcr Activationsupporting
confidence: 59%
“…Removal of Latrophilin/CIRL results in a dramatic drop of this input-output relationship leading to profound insensitivity toward mechanical stimulation and blurred signal-to-noise discrimination. Genetic experiments have further indicated that Latrophilin/CIRL may act by modulating ionotropic mechanosensors of the transient receptor potential channel family and may impinge on their properties in a mechanostimulus-dependent manner (see also Langenhan et al, 2015). Whether this effect of Latrophilin/CIRL is dependent on NTF, CTF, or both aGPCR fragments acting together remains to be determined.…”
Section: In Vivo Mechanisms Of Agpcr Activationmentioning
confidence: 99%
“…Characterization of these parameters for new compounds promises to be a means of discovering more efficacious GPCR drugs with fewer side effects. Also, it is important to recognize that the effects of native GPCRs may not always be extrapolated from in vitro data; the appropriate selection of model in vivo systems and organisms is important [48]. Furthermore, the expression pattern and physiological roles of a given GPCR can be altered in a disease state [141].…”
Section: New Pharmacological Dimensionsmentioning
confidence: 99%
“…Genetic variants of the unsaturated fatty acid receptor GPR120 have differential effects on obesity, both in humans (e.g. obesity-associated p.Arg270His mutation) and dogs, which can have implications for therapeutics and nutrition [48]. The encoding of µOR variants by the gene Oprm1 is subject to extensive alternative splicing, including C-terminal truncations.…”
Section: New Pharmacological Dimensionsmentioning
confidence: 99%
“…interpretation of GPCR crystal structures, importance of ligand residence time, GPCR multimers, the promise of biased signaling in vivo, spatial and temporal aspects of GPCR signaling, studying GPCR signaling with resonance energy transfer biosensors in vivo, model organisms in GPCR research, and a novel class of adhesion GPCRs and GPCR signaling networks from a systems biology perspective Langenhan et al, 2015;Lohse and Hofmann, 2015;Luttrell et al, 2015;Monk et al, 2015;Piscitelli et al, 2015;Roth et al, 2015;van Unen et al, 2015;Vischer et al, 2015). Scientists with expertise in in vitro and in vivo GPCR studies participated in the different reviews, thus bridging these fields.…”
mentioning
confidence: 99%